TRANSFORMATION OF STATE CONTROL TODAY - Zhurynov G.M.; Abylkasym A.B.; Syzdykov B.Sh.; Mashirova T.N.; Erzakova S.O. (Academic Journal of Physical and Chemical Sciences, 2020)
In most of the advanced countries of the world, the transition of the public administration system to "digital rails" is quite slow, and the development is far behind the officially defined and announced schedules. In this regard, the assessment of the effectiveness of digital management becomes particularly relevant. The effect of digitalization of public administration is often equated with an increase in its quality and a reduction in cost. The effect of digitalization of public administration is mainly associated with improving its quality and reducing costs. However, while research is being conducted on the quality of digitalization, a proper assessment methodology has not yet been developed on the issue of cost. Analysis of efficiency of public administration requires the determination, on the one hand, a clear relationship between the activities of civil servants and effectiveness of their work and, on the other hand, it is equally clear justification of expenditure on public administration and the amount of economic impact from the introduction of new services and technologies. State control is internal and external control, control and supervision of structural and territorial units, subordinate state bodies and organizations, aimed at ensuring compliance with decisions made by state bodies, as well as requirements, verification and conformity control. Unresolved issues lead to inefficient use of resources, incomplete implementation of the country’s socioeconomic development opportunities, and insufficient public confidence in state institutions The article provides a brief description of the systemic problems of public administration and control in Kazakhstan, highlights the main reasons for ineffective audit of state bodies. The problems of improving the system of state control in Kazakhstan and improving the efficiency of Executive authorities that can be solved using digital technologies, what restrictions are there, and how they can be overcome are considered.